Ranibizumab in the Treatment of Diabetic Macular Edema: A Review of the Current Status, Unmet Needs, and Emerging Challenges - Dervenis, Nikolaos (Adv Ther, 2017)
Diabetic retinopathy (more specifically diabetic macular edema, DME) is the most common cause of loss of vision in the working population in developed countries. Anti-vascular endothelial growth factor (anti-VEGF) agents considerably changed the treatment algorithms and improved prognosis of center-involving DME. Ranibizumab was the first approved anti-VEGF agent that revolutionized DME treatment. The vast increase in the number of patients undergoing intravitreal treatment and the role of anti-VEGF pharmacotherapy as the mainstay of DME treatment have triggered several challenges. Among them, of considerable interest is the quest for an optimal dosing scheme and the search for combination therapies. Although a significant body of research is directed towards other molecules that could potentially be new therapeutic targets, VEGF inhibition is expected to play an important long-term role in the treatment of DME considering the pathogenesis of the disease. Finally, recent studies revealed that ranibizumab may constitute a significant treatment modality in the management of other diabetic vision-threatening complications including proliferative diabetic retinopathy.